T-cell Activation Induces Dynamic Changes in miRNA Expression Patterns in CD4 and CD8 T-cell Subsets - Teteloshvili, Nato; Smigielska-Czepiel, Katarzyna; Kroesen, Bart-Jan; Brouwer, Elisabeth; Kluiver, Joost; M. H. Boots, Annemieke; van den Berg, Anke (MicroRNA, 2015)
T-cell activation affects microRNA (miRNA) expression in T-cell subsets. However, little is known about the kinetics of miRNA regulation and possible differences between CD4 and CD8 T cells. In this study we set out to analyze the kinetics of activation-induced expression regulation of twelve pre-selected miRNAs. The dynamics of the expression of these miRNAs was studied in sorted CD4 and CD8 CD45RO- T cells of healthy individuals stimulated with αCD3/αCD28 antibodies. Analysis of miRNA levels at day 3, 5, 7 and 10 showed significant activation-induced changes in expression levels of all twelve miRNAs. Expression levels of nine miRNAs, including miR-21, miR-146a and miR-155, were induced following activation, whereas expression of three miRNAs, including miR-31, were decreased following activation. The expression changes of miR-18a and miR-155 was relatively early, at day 3, whereas expression of miR-451, miR-21 and miR-146a was evident at day 5, 7 and 10, respectively. Four miRNAs showed a differential regulation between CD4 and CD8 T cells. Induction of miR-18a and miR-21 was more pronounced and occurred earlier in CD4 T cells compared to CD8 T cells. Downregulation of miR-223 and miR-451 was also more pronounced in CD4 T cells compared to CD8 T cells. In conclusion, we show a complex pattern of miRNA expression regulation upon T-cell activation with early and late as well as CD4 and CD8 T-cell specific changes. These differences might be the result of differences in kinetics and efficiency of CD4 and CD8 T cells in response to antigen priming.
Keywords: immune